The acceptance of the trainee counsellors towards Smart Counselling Management System (SCMS) - Wan Jaafar, Wan Marzuki; Ismail @ Mat Jusoh, Normazlina; Abdullah, Borhannudin; Mohd Ayub, Ahmad Fauzi (Elsevier, 2012)
Awareness that the progress of information technology can improve productivity. Along with the need for increased counseling services from time to time have led to the development of the counseling management system know as the Smart Counseling Management System (SCMS). This study was carried out to see how far the level of consumer acceptance of this system using the Technology Acceptance Model (TAM). The respondents are trainee counselor. A set of questionnaire was used to measure the acceptance towards SCMS. The data was analyzed by using descriptive method to describe the respondents’ level of acceptance of SCMS. The results showed that the acceptance of respondents are positive and are at high levels. Overall, this study has clarified that the system was able to achieve its development objectives.